Blood mononuclear cell molecular landscape associated with tumor progression in triple-negative breast cancer - M. R. Patysheva; A. A. Frolova; O. D. Bragina; A. A. Fedorov; M. A. Vostrikova; E. Yu. Garbukov; P. S. Iamshchikov; M. Vashisth; N. V. Cherdyntseva; T. S. Gerashchenko (Сибирский онкологический журнал)
Introduction. triple negative breast cancer is an aggressive clinical phenotype characterized by poor prognosis. immune system plays an important role in the development, treatment response, and progression of solid tumor. The search for immune-related markers associated with the prediction of treatment efficacy and disease prognosis, and based on the use of high-resolution molecular techniques, is a promising area of research, the results of which can be translated into clinical practice. Case description. The molecular profile of blood mononuclear cells in a 48-year-old female patient with histologically proven triple negative breast cancer (estrogen Receptor – 0; progesteron Receptor – 0; Her2/neu – 0; gata-3 – 0, androgen Receptor – 0 and Ki67 – 70 %) was described. The patient did not response to neoadjuvant chemotherapy with 4 cycles of paclitaxel + carboplatin followed by 2 cycles of adriamycin + cyclophosphamide. The patient underwent surgery. disease progression (pelvic bone metastases) occurred 2 months after surgery. The features of blood lymphocytes and monocytes associated with a lack of response to neoadjuvant chemotherapy and disease progression were described.Conclusion. This clinical case demonstrates that sequencing of peripheral blood mononuclear cells can be used as a method for identifying predictive markers of therapy efficacy and developing personalized treatments for patients with triple negative breast cancer.